2013
DOI: 10.1111/acel.12072
|View full text |Cite
|
Sign up to set email alerts
|

Balance between autophagic pathways preserves retinal homeostasis

Abstract: Summary Aging contributes to the appearance of several retinopathies and is the largest risk factor for aged-related macular degeneration, major cause of blindness in the elderly population. Accumulation of undegraded material as lipofuscin represents a hallmark in many pathologies of the aged eye. Autophagy is a highly conserved intracellular degradative pathway that plays a critical role in the removal of damaged cell components to maintain the cellular homeostasis. A decrease in autophagic activity with age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
155
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(174 citation statements)
references
References 35 publications
5
155
1
5
Order By: Relevance
“…It was recently reported that the age-dependent decrease in macroautophagy in the retina was accompanied by a concomitant increase in CMA to help preserve the retina. 22 We found no evidence for increased CMA in retina when Atg5 was deleted in rods as determined by measuring the levels of Lamp2A and Hsc70. It should be noted that in this previous study involving retinal aging, Atg5 was deleted using a NestinCre that deletes Atg5 in all neural precursors beginning at embryonic day 10.5.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…It was recently reported that the age-dependent decrease in macroautophagy in the retina was accompanied by a concomitant increase in CMA to help preserve the retina. 22 We found no evidence for increased CMA in retina when Atg5 was deleted in rods as determined by measuring the levels of Lamp2A and Hsc70. It should be noted that in this previous study involving retinal aging, Atg5 was deleted using a NestinCre that deletes Atg5 in all neural precursors beginning at embryonic day 10.5.…”
Section: Discussioncontrasting
confidence: 57%
“…54 Thus, in the retina, Atg5 deletion would occur in rods, Mueller cells, RPE cells, cones, ganglion cells, bipolar cells, etc. making it difficult to determine whether the degenerative effects on the retina or the increase in CMA observed by these authors 22 were the result rod photoreceptor-specific deletion of Atg5 or the cumulative effects of Atg5 deficiency in the other cell types.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations